2005 IEEE Conference on Emerging Technologies and Factory Automation
DOI: 10.1109/etfa.2005.1612749
|View full text |Cite
|
Sign up to set email alerts
|

Control Software Reuse Strategies with IEC 61499

Abstract: The IEC 61499 gives developers considerable freedom and offers several features that support reuse.Although this can help the adoption of the standard into an organization's development process, the range of design decisions can also harm the reusability of software, ifcomponents are developed with incompatible design principles. Guidelines are needed, but the unique backgrounds and market positions of industrial players must be respected. The paper analyzes some alternative solutions that were developed by au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Even software design patterns for IEC 61499 programs, e.g., Distributed Application, Proxy and Model-View-Controller, were defined (Christensen, 2000) and evaluated (Strömman et al, 2005). However, although IEC 61499 runtimes on state of the art controllers exist (Vyatkin, 2011), "IEC 61499 has a long way in order to be seriously considered by the industry" (Thramboulidis, 2013).…”
Section: State Of the Artmentioning
confidence: 98%
“…Even software design patterns for IEC 61499 programs, e.g., Distributed Application, Proxy and Model-View-Controller, were defined (Christensen, 2000) and evaluated (Strömman et al, 2005). However, although IEC 61499 runtimes on state of the art controllers exist (Vyatkin, 2011), "IEC 61499 has a long way in order to be seriously considered by the industry" (Thramboulidis, 2013).…”
Section: State Of the Artmentioning
confidence: 98%
“…The same challenge occurs with case studies testing industrial experts and/or researchers as e.g. described in [27] and [28]. In both studies, a significant small group of participants were observed during courses on programming in accordance to the IEC 61499 compared to IEC 61131-3 standard and an Object Oriented approach.…”
Section: Methods In Usability Evaluationmentioning
confidence: 98%
“…Using different notations modeled solutions are different two regarding number of nodes and edges of the correct master model (see Appendix B for an example). As Strömmann [27] already realized often different correct solutions are created by different subjects, which should be evaluated equally good. Moreover, equality of nodes in a class diagram (abstract representation) and nodes and edges in an activity diagram (low level, object related) are rated equally by Schalles.…”
Section: Effectiveness-quality Of the Resulting Model Programmentioning
confidence: 99%
See 1 more Smart Citation
“…This added freedom of design can be used to increase advantages in several areas as decentralization, reuse, flexibility, optimization, formal verification et.c. For example the solutions can be designed for different kind of reusability goals [21].…”
Section: Introductionmentioning
confidence: 99%